UNDERSTANDING HUMAN RIGHTS IN ISLAM: THE IDEAS OF ABDULLAH BIN BAYYAH - Haidar Masyhur Fadhil (UIN ANTASARI BANJARMASIN, 2023)
This article explores Abdullah bin Bayyah's views on human rights within the context of Islam. Bin Bayyah is a prominent Islamic scholar who emphasizes the compatibility between Islamic teachings and universal human rights, challenging misconceptions and fostering dialogue. The article examines Bin Bayyah's core beliefs on human rights in Islam, emphasizing the importance of understanding Islamic principles within their historical and cultural context. It highlights the universality and inclusivity of human rights in Islam, promoting the inherent dignity and worth of all individuals, irrespective of their race, gender, or religion. The article also explores various aspects of human rights in Islam, including freedom of conscience, women's rights, and religious pluralism, and how his interpretations align with contemporary human rights standards. The article critically analyzes potential areas of tension between Islamic teachings and human rights principles, highlighting the need for informed dialogue and contextual interpretations to address these complex issues effectively. Overall, the article aims to shed light on Bin Bayyah's contributions to the discourse on human rights in Islam, emphasizing the importance of an inclusive and comprehensive understanding of Islamic teachings that respects the fundamental rights and freedoms of all individuals.